A data-hiding technique with authentication, integration, and confidentiality for electronic patient records. - Hui-Mei Chao
A data-hiding technique called the "bipolar multiple-number base" was developed to provide capabilities of authentication, integration, and confidentiality for an electronic patient record (EPR) transmitted among hospitals through the Internet. The proposed technique is capable of hiding those EPR related data such as diagnostic reports, electrocardiogram, and digital signatures from doctors or a hospital into a mark image. The mark image could be the mark of a hospital used to identify the origin of an EPR. Those digital signatures from doctors and a hospital could be applied for the EPR authentication. Thus, different types of medical data can be integrated into the same mark image. The confidentiality is ultimately achieved by decrypting the EPR related data and digital signatures with an exact copy of the original mark image. The experimental results validate the integrity and the invisibility of the hidden EPR related data. This newly developed technique allows all of the hidden data to be separated and restored perfectly by authorized users.
Keywords: Internet; Authentication; Bipolar multiple number base; Confidentiality; Data-hiding technique; Diagnostic reports; Digital signatures; Doctors; Electrocardiogram; Electronic patient records; Hospital; Integration; Mark image; Medical data